2010
DOI: 10.1027/1901-2276/a000011
|View full text |Cite
|
Sign up to set email alerts
|

Gendering late-life depression? The coping process in a group of elderly men

Abstract: The increase in suicide rates in older men poses a serious challenge in terms of better detection and diagnosis of depression, as the increase could suggest that there are a number of aging, depressive men who are not diagnosed and therefore remain untreated for their depression. This study is an interview study with 8 elderly men (between 66 and 85 years of age) diagnosed with depression in late-life. It examines how the men discuss, perceive and act in relation to stressful situations in late life, and how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…The MDS may provide additional clinical information in women in addition to men. The finding that masculine traits are associated with lower levels of typical depressive symptomspartially corroborates previous qualitative and theoretical work (Chuick et al, 2009;Jensen et al, 2010;Rochlen et al, 2010). Magovcevic and Addis (2008) reported that two measures of hegemonic masculinity were moderately and positively associated with greater scores on several measures of depressive symptoms, including the externalizing subscale of the MDS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The MDS may provide additional clinical information in women in addition to men. The finding that masculine traits are associated with lower levels of typical depressive symptomspartially corroborates previous qualitative and theoretical work (Chuick et al, 2009;Jensen et al, 2010;Rochlen et al, 2010). Magovcevic and Addis (2008) reported that two measures of hegemonic masculinity were moderately and positively associated with greater scores on several measures of depressive symptoms, including the externalizing subscale of the MDS.…”
Section: Discussionsupporting
confidence: 88%
“…With the exception of Jensen et al (2010), who provided qualitative support for gendered responding through interviews with older men who had been depressed, there have been few publications relevant to older adults. Systematic interviews with clinicians and clinical researchers have suggested that depressed older men deny experiencing depressive or psychological symptoms but endorse sleep, cognitive, and pain symptoms and are therefore difficult to diagnose or refer to appropriate psychological treatment (Hinton, Zweifach, Oishi, Tang, & Unuetzer, 2006).…”
Section: Applying Gendered Responding To Older Adultsmentioning
confidence: 99%
“…The themes discussed above are consistent with other reports on depression and anxiety in the elderly (Hinrichsen, 2008;Jensen, Munk, & Madsen, 2010;Schwartz, 2004).…”
Section: Clinical Vignettes and Common Therapy Issuessupporting
confidence: 89%
“…Considering that older men are at serious risk for suicide, it is encouraging to see that men accessed our group program and benefited. A recent Danish study showed that men tended to use fewer coping strategies and used mainly those aimed at continuing life as it was before they reached this older age-or to maintain that illusion (Jensen, Munk, & Madsen, 2010). Until acceptance has taken place, new commitments and purpose in life cannot be met by the individual.…”
Section: Discussionmentioning
confidence: 99%
“…* By comparison, there is some suggestion that men may be somewhat more prone to cope by distancing from stress-related negativity. 50 Clearly, this area merits more attention.…”
Section: The Developmental Contextmentioning
confidence: 99%